The effect of ultrasound-assisted vacuum drying on the drying rate and quality of red peppers - Tekin, Zeynep Hazal; Baslar, Mehmet (SPRINGER, 2018)
Ultrasound-assisted vacuum (USV) drying is a promising method to increase heat and mass transfer rate. This study aimed to examine effects of USV drying on the drying rate and some quality parameters of red peppers at 45, 55, 65, and 75 A degrees C. The results were compared with USV control drying (vacuum drying without ultrasound treatment) and the other drying methods. The USV drying shortened the drying period to 25% and increased the effective moisture diffusivity (D (eff)) to 89% when compared by USV control drying. The dehydration kinetics of the red peppers were successfully described using seven thin layer drying models for all of the dehydration methods, and the logarithmic model had the best fit for the USV drying, with highest R (2) and lowest RMSE values. The total yeast and mold counts were significantly reduced following the USV drying in comparison with the USV control drying. This study suggested that USV drying could be used effectively in drying of red pepper with high drying rate and no significant bioactive compound degradation compared to USV control.
Keywords: Ultrasound-assisted vacuum (USV) drying; Red peppers; Dehydration rate; Rehydration ratio; Mold and yeast; PHYSICOCHEMICAL PROPERTIES; ANTIOXIDANT CAPACITY; MOISTURE DIFFUSIVITY; DATA COMPILATION; CAPSICUM-ANNUUM; APPLE JUICE; KINETICS; COLOR; L.; PRETREATMENT; Thermodynamics; Chemistry